2017
DOI: 10.17265/2332-7839/2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reproducibility of the Garmin Vector Power Meter When Compared to the SRM Device

Abstract: Abstract:Mobile power meters allow for cyclists to monitor power output (PO) during training and competition. The Garmin Vector power meter (VPM) measures PO at the pedal compared to the crank and has been tested in only a few limited studies. The purpose of this study was to determine the validity and reproducibility of the VPM by comparing it to the SRM. The VPM validity was tested by (1) a submaximal incremental test, (2) submaximal constant power test, (3) sprint test, and (4) a field test. The reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The effects of position on PO measurements have been tested in several studies [ 36 , 51 , 69 , 77 , 89 , 94 , 106 ] to assess the sensitivity of power meters. Bertucci, Duc, Villerius, Pernin, and Grappe [ 36 ] reported that the PowerTap rear hub was not significantly affected by the position change (standing vs. seated) when compared to the SRM power meter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of position on PO measurements have been tested in several studies [ 36 , 51 , 69 , 77 , 89 , 94 , 106 ] to assess the sensitivity of power meters. Bertucci, Duc, Villerius, Pernin, and Grappe [ 36 ] reported that the PowerTap rear hub was not significantly affected by the position change (standing vs. seated) when compared to the SRM power meter.…”
Section: Discussionmentioning
confidence: 99%
“…The number of participants and their characteristics are very important for integrating the results that were obtained. Some studies used only one participant during the measurement process [ 36 , 51 , 77 , 88 , 89 ]. In this situation, the authors consider that differences in the pedalling technique between the athletes or patients does not affect the accuracy of measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation